Allosteric regulation of αIIbβ3 by β3 95–105 - Haas, Thomas A. (Thrombosis and Haemostasis, 2008)
The linear recognition sequences of an anti-β3 antibody that blocked platelet aggregation were identified using β3 tryptic peptides. Two of these recognition sequence-containing peptides were mapped to β3 92–105, and antibodies affinity purified using these peptides blocked platelet aggregation. Examining the structure of αIIbβ3 identified β3 95–105 as the solvent accessible sequence within β3 92–105. A peptide corresponding to β3 95–105 was synthesized and used to affinity purify the β3 antibody. Anti-β3 95–105 completely blocked platelet aggregation and agonist-induced fibrinogen binding to platelets, but had no effect on cyclic-RGD binding. Binding of anti-β3 95–105 to αIIbβ3 also did not alter the structure of the αIIb cap subdomain, as measured by anti-αIIb 201–217 binding. β3 95–105 and peptides spanning two adjacent sequences in the structure of β3 did not bind fibrinogen and were ineffectual in blocking agonist-induced platelet aggregation. Structure analysis revealed that β3 95–105 is adjacent to one of the two hinges in β3 that allows for the outward swing of the hybrid and PSI domains which is central to the conversion of αIIbβ3 from a low into a high affinity state.Thus, the binding of an antibody to β3 95–105 could serve as a fulcrum for allosteric regulation of αIIbβ3 by regulating the movement of the hybrid-PSI domain.
Keywords: Antiaggregatory agents; fibrinogen binding; GPIIb/IIIa inhibitors; platelet activation inhibitors